Indocyanine green clearance test to evaluate liver function in rat model of extrahepatic biliary atresia - Hemonta Kr Dutta; D N Rao; D K Gupta (Wolters Kluwer Medknow Publications, 2018)
Background: Indocyanine green clearance test (ICG-K) has been shown as a sensitive marker of liver function in patients with cirrhosis. However, its role in the assessment of liver function in children with biliary atresia is not well established. The present study was undertaken to evaluate the ICG-K in an experimental model of cholangitis and partial biliary obstruction. Materials and Methods: Thirty albino rats were divided into 3 groups of 10 each. After exploration under anesthesia, a vial of OK-432 diluted in 0.2 ml of normal saline was injected into the common bile duct (CBD) in rats of Groups B and C. In the control Group A, only saline was injected. Re-exploration was done at 3 weeks in Groups A and B and at 6 weeks in Group C, and freshly prepared ICG was injected into the inferior vena cava. Blood samples were collected at periodic intervals, optical density of the serum was measured, and half-life of ICG and fractional clearance (K) were calculated. Blood and tissue samples were obtained for biochemical tests and histological examination. Results: The histological changes in CBD and liver were maximum in Group B; this correlated well with the K-value in this group, which was significantly delayed. In Group C, clearance was delayed than the control group with histological changes ranged from mild to moderate inflammation. The control group had normal histology of liver and CBD, and only four rats showed mild portal inflammation. Conclusion: ICG clearance rate is a reliable marker of liver function and can be utilized for evaluation of liver function in postoperative extrahepatic biliary atresia patients.